Neighbours' Conviviality without Gatherings. Social Streets in Times of Lockdown - Fabio Introini; Niccolò Morelli; Cristina Pasqualini (Partecipazione e Conflitto, 2021)
The lockdown period imposed by Italian institutions to their citizens from March to May 2020 to contrast the Coronavirus diffusion had a very deep impact on people's sociality and their daily practices. However, informal groups and associations tried to keep them alive with the help of digital communication technologies, used to enhance conviviality and to support and organize forms of mutual help. This article aims to analyse how Social Streets promoted sociality and mutual help among neighbours in time of lockdown, and how Streeters, here defined as people who are at least inscribed at the Facebook group of their Social Street, have profited from the possibility to have at their disposal an online social place where to interact and be informed about the possibility of giving and receiving help. This article draws from data gathered through two online surveys, administered, respectively, during lockdown phase in the second half of April (838 respondents) and in June 2020, after its end (371 respondents). Our results show that, after seven years since their foundation in 2013, Social Streets still play a pivotal role in the neighbourhood. During lockdown, they gave a contribution in keeping neighbours informed about what was going on in the neighbourhood, in sustaining and producing convivial ties, in organizing mutual help services. In the hard time of lockdown, when most of the usual habits and practices were forcefully suspended, Social Streets proved very important in setting a cognitive, emotional, and organizational framework inside which conviviality and collaboration among neighbours could find greater plausibility.